2021
DOI: 10.1126/science.abc6108
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a choroid plexus vascular barrier closing during intestinal inflammation

Abstract: Locking down access to the brain Inflammatory bowel disease is best known for intestinal symptoms but can also cause a variety of extraintestinal manifestations in other organs. It can also be associated with cognitive and psychiatric effects, including anxiety and depression. Using mouse models of intestinal inflammation, Carloni et al . uncovered a potential pathogenic link between these aspects of inflammatory bowel disease. The inflammatory process causes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
152
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(157 citation statements)
references
References 76 publications
(80 reference statements)
4
152
1
Order By: Relevance
“…In this case, the monitoring of Gram-negativity could suggest a change to a less inflammatory diet such as the Mediterranean one [99]. Based on a recent publication that demonstrates how intestinal microbiota-derived LPS can contribute to anxious-depressive manifestation [100], analysis of the G+/G− ratio could help the physician in deciding whether to set up a conventional-only therapy (with anti-depressants and/or anxiolytics) or whether to intervene also on the diet trying to reduce the total Gramnegativity. Even if the Prevotella content in people of industrialized countries is certainly modest, the P/B ratio could also be advantageously applicable in diets.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the monitoring of Gram-negativity could suggest a change to a less inflammatory diet such as the Mediterranean one [99]. Based on a recent publication that demonstrates how intestinal microbiota-derived LPS can contribute to anxious-depressive manifestation [100], analysis of the G+/G− ratio could help the physician in deciding whether to set up a conventional-only therapy (with anti-depressants and/or anxiolytics) or whether to intervene also on the diet trying to reduce the total Gramnegativity. Even if the Prevotella content in people of industrialized countries is certainly modest, the P/B ratio could also be advantageously applicable in diets.…”
Section: Discussionmentioning
confidence: 99%
“…The BBB alteration has been clearly confirmed whereby versatile methods, including blue Evans, fluorescent-labeled dextran clearance, labeled granulocytes, electron microscopy, and magnetic resonance imaging in sepsis models and also in patients (Papadopoulos et al, 1999;Esen et al, 2005Esen et al, , 2012Sharshar et al, 2007;Handa et al, 2008;Bozza et al, 2010). Furthermore, a recent study has confirmed that BBB displayed a short-term closure at the early stage of inflammation and gradually opened up as the disease progressed (Carloni et al, 2021). Nonetheless, it eventually allows for the entry of neurotoxic molecules, particularly inflammatory mediators, consequently giving rise to brain cell death in systemic inflammation.…”
Section: Sepsis-associated Inflammatory Signals To Central Nervous System Enhanced On Intracerebral Hemorrhagementioning
confidence: 77%
“…This results in increased translocation of gut-and microbiota related metabolites from the lumen of the gut to the bloodstream and eventually the brain, accompanied by an increased inflammatory response (Bischoff et al, 2014). Recently, Carloni et al showed that inflammation originating in the gut can induce propagation of the inflammation to the brain via increasing permeability of the blood-brain barrier, which may be responsible for the observed mental symptoms in individuals with inflammatory bowel disease (Carloni et al, 2021). Indeed, abnormal immune responses have been reported both in patients with SSD and BD, of varying disease stages and medication status (Beumer et al, 2012;Horváth and Mirnics, 2014;Muller and J. Schwarz, 2010;Munkholm et al, 2013).…”
Section: Discussionmentioning
confidence: 99%